CONSIDERAZIONI IN MERITO ALLA PROTEZIONE DEI POLLI ALLEVATI PER LA PRODUZIONE DI CARNE (BROILERS) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The Legislative Decree. n. 181 of 27 September 2010, Implementation of Directive 2007/43/EC regarding minimum standards for the protection of broilers kept for meat production, sets out specific requirements for the welfare of chickens kept for meat production, in conjunction with the general dictates of Legislative Decree n. 146/2001 regarding the welfare of farmed animals. Within 60 days since its publication, the Ministry of Health should have issued a more specific implementing decree, in order to regulate in particular the breeding density. The implementing decree has not been published yet, but it would also be appropriate to provide consistent application guidelines even on other issues, such as staff education, surgery and animal welfare control.